Predictive Factors for Clinical Outcome After Direct Mechanical Thrombectomy for Anterior Circulation Large Vessel Occlusion Within 4.5 h - Nguyen, Huu An; Vu, Dang Luu; Nguyen, Quang Anh; Mai, Duy Ton; Tran, Anh Tuan; Le, Hoang Kien; Nguyen, Tat Thien; Nguyen, Thu Trang; Tran, Cuong; Dao, Viet Phuong; Pierot, Laurent (Frontiers in Neurology, 2022)
Background Recent trials including DIRECT-MT, DEVT, and SKIP have found that direct mechanical thrombectomy (MT) is equally effective as the combination of MT and intravenous thrombolysis. However, the results of the other trials, namely MR-CLEAN NO-IV and the SWIFT-DIRECT trial have failed to confirm the non-inferiority of direct MT vs. the combination therapy. Aim We aimed to identify prognostic factors of direct MT for anterior circulation large vessel occlusion within 4.5 h. Materials and Methods Data from January 2018 to January 2022 were retrospectively collected and analyzed. Adult patients with confirmed anterior circulation large vessel occlusion within 4.5 h of onset with baseline NIHSS of ≥6 and baseline ASPECTS of ≥6 treated using direct MT within 6 h were recruited. Results A total of 140 patients were enrolled in the study with a median age of 65.5 years [interquartile range (IQR), 59–76.5], median baseline NIHSS of 13.5 (IQR, 11–16), and median baseline ASPECTS of 8 (IQR, 7–8). Direct MT was feasible in all patients (100%). Successful reperfusion (mTICI 2b-3) was achieved in 124/140 patients (88.6%) with a low rate of complications (8/140, 5.7%). Any type of intracranial hemorrhage (ICH) and symptomatic ICH occurred in 44/140 (31.4%) and 5/140 (3.6%), respectively. Overall, a good outcome (mRS 0–2) was achieved in 93/140 (66.4%), and the mortality rate was 9.3% (13/140 patients). Using multivariate analysis, lower age [odds ratio (OR), 0.96; 95% CI, 0.92–1.00; P = 0.05], low baseline NIHSS (OR, 0.82; 95% CI, 0.74–0.92; P = 0.00), and absence of ICH (OR, 0.29; 95% CI, 0.10–0.81; P = 0.02) were independently associated with favorable outcome. Independent predictors of mortality were baseline NIHSS (OR, 1.21; 95% CI, 1.01–1.46; P = 0.04), successful reperfusion (OR, 0.02; 95% CI, 0.00–0.58; P = 0.02), and ICH (OR, 0.12; 95% CI, 0.02–0.75; P = 0.02). Further analysis showed that the median mRS at 90 days was significantly better in the MCA occlusion group compared to the ICA plus M1 occlusion group [1 (IQR 0–3) vs. 2 (IQR 1–4); P = 0.05]. Conclusions Our findings suggest that direct thrombectomy may be an adequate clinical option for younger patients (≤70) experiencing proximal middle artery occlusion within 4.5 h and who have low baseline NIHSS (≤14).